Development of Google Form-based Digital Worksheets to Increase the Learning Spirit of High School Students - Harun, Fadilah; Rusli, Hildawati; Wahyuni, Sri; Marwiyah; Sudirman (South Sulawesi Education Development, 2024)
This study aims to produce a Valid and Practical Google Forms-based Digital Worksheet to enhance the Learning Enthusiasm of High School Students. The method used is Research and Development with the ADDIE design, focusing on the development of digital worksheets with both validity and practicality. The ADDIE design stages involve analysis, design, development, implementation, and evaluation. The research was conducted at State High School 3 Luwu, involving 20 students as participants. Data were collected through observation and questionnaires. The questionnaires were used for validation by subject matter experts and media experts, using a rating scale of 1-5. Additionally, the questionnaires assessed student responses to the digital worksheets after the trial, using the same rating scale. Data were processed through descriptive statistical and qualitative descriptive analysis. The research results showed material validity of 86% and media validity of 95%, providing a strong foundation for the use of technology in learning. Student responses obtained an average percentage of 85.14%, indicating that the digital worksheets were highly practical.